1998
DOI: 10.1002/(sici)1096-9071(199812)56:4<327::aid-jmv7>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Concanavalin A-immobilized polystyrene nanospheres capture HIV-1 virions and gp120: Potential approach towards prevention of viral transmission

Abstract: To establish an effective tool for the prevention of HIV-1 transmission, lectin-immobilized polystyrene nanospheres were synthesized and examined for their HIV-1 capture activity. When concanavalin A (Con A) was immobilized on the surface of polystyrene nanospheres (400 nm in diameter) with poly(methacrylic acid) branches and incubated with HIV-1 suspension at room temperature for 60 min, the nanospheres (Con A-NSs) achieved a >3.3 log and a 2.2 log reduction of viral infectivity in HIV-1 (IIIB strain) suspens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 23 publications
(19 reference statements)
0
27
0
Order By: Relevance
“…Its original function is believed to be an antiprotease defense against neutrophils at the mucosal surfaces (155). In vitro laboratory studies have shown that SLPI can inhibit HIV entry into CD4 + cells by interacting with targeted cells blocking access as a barrier function.…”
Section: A Secretory Leukocyte Protease Inhibitormentioning
confidence: 99%
See 1 more Smart Citation
“…Its original function is believed to be an antiprotease defense against neutrophils at the mucosal surfaces (155). In vitro laboratory studies have shown that SLPI can inhibit HIV entry into CD4 + cells by interacting with targeted cells blocking access as a barrier function.…”
Section: A Secretory Leukocyte Protease Inhibitormentioning
confidence: 99%
“…This may provide a reason as to the low rate of HIV infection through oral sex due to the presence of SLPI in saliva. Data from studies of various mucosal tissues such as the mouth, gut, rectum and endocervix, suggest an inverse relationship between infectious HIV and the presence of SLPI (155). Further studies of SLPI as "a natural endogenous product" need to be performed since it has been shown to have the potential to function as an effective microbicide (155)(156)(157).…”
Section: A Secretory Leukocyte Protease Inhibitormentioning
confidence: 99%
“…22,23 Lectins have been covalently conjugated to a poly-(methacrylic acid) corona of the same polySt core and used to capture HIV-1 gp120 and virions with the interaction between lectins on the nanosphere and mannose of gp120. 17,18 Lactose has also been covalently bonded to a poly(vinylamine) corona of the same core and used to recognize a lectin. 24,25 Very recently, we directly observed cross-sectional morphologies of core-corona nanospheres by transmission electron microscopy (TEM).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported that Con A-immobilized polystyrene NPs could efficiently capture HIV-1 particles and gp120 Ags (20). Immunization with inactivated HIV-1-capturing NPs induced HIV-1-specific IgA Abs in the genital tract of mice (21,22).…”
mentioning
confidence: 97%